ANALISA FLUKTUASI NOMINAL SAHAM RESULTAN PUBLIKASI LAPORAN KEUANGAN INTERIM Di BURSA EFEK INDONESIA - Martias, Andi; Sudirja, Sudirja (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
The current development of the stock market attracts the attention of capital owners or investors to invest in the stock market. Stock exchange participants can buy and sell shares or other things on the Indonesia Stock Exchange (IDX). Effect of financial reports on company stock prices on the IDX. Fluctuating stock prices are a problem faced by investors today, therefore investors must be careful in making decisions. Every investor decision making should be based on good financial reports. This study aims to determine the possible influence of interim financial reports on changes in stock prices on the IDX. The research method uses the Minitab program analysis, as well as applying samples to companies on the IDX. The population of this study is companies registered on the IDX in the period 2018 to the end of 2022, and publishing interim financial reports electronically and in the mass media, no later than 120 days after closing the company's books. So that in this study took a sample of 53 most active companies. The data in this research are secondary, taken from literature and data sources published by the Indonesia Stock Exchange (https://old.idx.co.id/). Tests on stock prices (P it), Abnormal Return (AR) both realized returns and expected returns and event dates. The results of calculations and analysis of data carried out in this study concluded that the publication of interim financial reports did not have a significant effect on changes in stock prices as a whole.